2020
DOI: 10.1007/jhep06(2020)062
|View full text |Cite
|
Sign up to set email alerts
|

Chiral perturbation theory for nonzero chiral imbalance

Abstract: We construct the most general low-energy effective lagrangian including local parity violating terms parametrized by an axial chemical potential or chiral imbalance µ 5 , up to O(p 4 ) order in the chiral expansion for two light flavours. For that purpose, we work within the Chiral Perturbation Theory framework where only pseudo-NGB fields are included, following the external source method. The O(p 2 ) lagrangian is only modified by constant terms, while the O(p 4 ) one includes new terms proportional to µ 2 5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Four different pion masses were explored: m π = (563, 762, 910) MeV. It was found that the model follows the chiral perturbation theory prediction [74] ρ 5 = Λ QCD µ 5 : the chiral density depends linearly on the chiral chemical potential, there are no thresholds. The study reveals that the topological susceptibility increases with the chiral chemical potential, much in the same way as the chiral condensate did in the two-color study.…”
Section: Chiral Densitymentioning
confidence: 96%
“…Four different pion masses were explored: m π = (563, 762, 910) MeV. It was found that the model follows the chiral perturbation theory prediction [74] ρ 5 = Λ QCD µ 5 : the chiral density depends linearly on the chiral chemical potential, there are no thresholds. The study reveals that the topological susceptibility increases with the chiral chemical potential, much in the same way as the chiral condensate did in the two-color study.…”
Section: Chiral Densitymentioning
confidence: 96%
“…where S eff is introduced in Eq. (16). In what follows we are going to investigate the dependence of the global minimum point of the function (M, π a ) vs chemical potentials.…”
Section: The Modelmentioning
confidence: 99%
“…So in the most general case the chiral imbalance of dense quark matter can be described by two different chemical potentials, chiral μ 5 and chiral isospin μ I 5 , which are conjugated to the above densities, n 5 and n I 5 , correspondingly. There is a significant number of studies [7][8][9][10][11][12][13][14][15][16][17], in which the influence of the chiral imbalance on the phase structure was considered only in the form of the chiral chemical potential μ 5 . And it is thought that this form of chiral imbalance can be generated in the fireball after heavy-ion collision as a consequence of the famous chiral Adler-Bell-Jackiw anomaly and it plays an important role in the chiral magnetic effect phenomenon [18], etc.…”
Section: Introductionmentioning
confidence: 99%
“…From the theoretical side, people use various methods to study the QCD phase diagram. Such as chiral perturbation theory [1], finite energy sum rules [2], Dyson-Schwinger equations [3][4][5], Nambu-Jona-Lasinio (NJL) model and Polyakov-Nambu-Jona-Lasinio (PNJL) [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%